Pengaruh Audit Tenure, Audit Fee, dan Ukuran KAP Terhadap Kualitas Audit - Putri, Andini Nurmalia; Astuti, Tutut Dewi (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the effect of audit tenure, audit fee, and KAP size on audit quality in financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. Using a quantitative approach with a sample of 280 secondary data observations, this study was analyzed using logistic regression analysis processed using SPSS 21 software. The results show that audit tenure has no effect on audit quality (significance value of 0.559 > 0.05). Conversely, audit fees have a negative effect with a significance value of 0.001 < 0.05, and KAP size has no effect on audit quality with a significance value of 0.830 > 0.05. These findings indicate that the higher the audit fee, the lower the audit quality produced due to agreements between auditors and clients that have the potential to reduce audit quality. Audit tenure and KAP size do not necessarily guarantee better audit quality.